Dampak CSR hijau dan investasi R&D hijau terhadap kinerja keuangan melalui penerapan ekonomi hijau - Eka Yuliyanti; Anis Turmudhi; Rahmania Mustahidda (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study examines the impact of Green Corporate Social Responsibility (CSR) and green Research and Development (R&D) investment on corporate financial performance through the mediating role of the green economy. The study population consisted of 228 manufacturing companies listed on the Indonesia Stock Exchange during the 2020–2024 period, with 72 companies selected as samples using secondary data obtained from annual reports, sustainability reports, financial reports, and PROPER ratings. Data testing was conducted using the SEM-PLS method. The results show that green CSR has a positive and significant impact on the implementation of the green economy, while green R&D investment has a negative but significant impact. Furthermore, neither green CSR nor green R&D investment has a direct impact on financial performance. The green economy actually has a negative but significant impact on financial performance, indicating the existence of a short-term cost burden from sustainable practices. These findings confirm the mediating role of the green economy and provide important input for companies and policymakers in balancing environmental responsibility with financial sustainability in emerging markets.